The Effect of Fiscal Rules on Public Investment if Budget Deficits are Politically Motivated - Robert A.J. Dur; Ben D. Peletier; Otto H. Swank (Tinbergen Institute, 1997)
Uncertainty about the future preferences of the government may induce policy makers to run excessive budget deficits. As a solution to this problem, economists have proposed to impose a binding debt rule. In this paper we argue that a binding debt rule does not eliminate the distortions due to strategic behaviour of politicians. Rather, strategic manipulation shifts from public debt to public investment. As an alternative, we examine the effects of a capital borrowing rule which permits the government to run a budget deficit equal to the amount of public investment. We show that this rule effectively eliminates strategic behaviour.
Keywords: D72; E62; H61; H62; 330; fiscal rules; budget deficits; public investment; Öffentliche Investition; Haushaltsdefizit; Finanzpolitik; Theorie